LED irradiation of halogen/nitrogen-doped polymeric graphene quantum dots triggers the photodynamic inactivation of bacteria in infected wounds. (15th April 2021) - Huang, Hao-Hsin; Anand, Anisha; Lin, Chin-Jung; Lin, Han-Jia; Lin, Yang-Wei; Harroun, Scott G.; Huang, Chih-Ching
Abstract: Graphene quantum dots (GQDs) are emerging disinfectants, owing to their distinctive photodynamic and antibacterial activities. Halogen-based antimicrobial materials are also known to be effective against infectious pathogens. In this work, we have developed visible light-activatable halogen/nitrogen co-doped polymeric graphene quantum dots [X/N–PGQDs, (X = Cl, Br, I)] as an antibacterial agent, prepared from spermidine and hydrohalic acid by a simple one-step heating method. We demonstrate that these high positively charged X/N–PGQDs are effective antibacterial agents (minimum inhibitory concentration (MIC) less than 0.5 μg mL −1 ) for the inhibition of both Gram-positive and Gram-negative bacteria. The antibacterial activities of X/N–PGQDs are enhanced upon exposure to white LED light irradiation due to the generation of reactive oxygen species (ROS) which induce oxidative stress, as well as physical disruption of the bacteria. Moreover, the MIC of X/N–PGQDs with LED light irradiation is 100-fold lower than in the dark, revealing their strong photo-induced inactivation of bacteria. X/N–PGQDs are effective for the eradication of multidrug-resistant bacteria in infectious wounds, even with just 1-min of irradiation. With their negligible cytotoxicity, we believe that X/N–PGQDs have great potential as a visible light-activated antibacterial nanomaterial for preclinical application in wound healing. Graphical abstract: Image 1 Highlights: Halogen/nitrogen co-doped polymeric graphene quantum dots (PGQDs) prepared by simple dry heating. PGQDs exhibit high affinity toward bacteria and superior photodynamic effects. The minimum inhibitory concentration of LED light-irradiated PGQDs for tested bacteria is down to 5 ng mL −1 . The removal rate in MRSA infected wound is >90% using PGQDs with only 1-min LED irradiation.